Information Hiding: Steganography and Watermarking-Attacks and Countermeasures Steganography and Watermarking - Attacks and Countermeasures - Johnson, Neil F.; Duric, Zoran; Jajodia, Sushil (Advances in Information Security, 2001)
Information Hiding: Steganography and Watermarking - Attacks and Countermeasures deals with information hiding. With the proliferation of multimedia on the Internet, information hiding addresses two areas of concern: privacy of information from surveillance (steganography) and protection of intellectual property (digital watermarking). Steganography (literally, covered writing) explores methods to hide the existence of hidden messages. These methods include invisible ink, microdot, digital signature, covert channel, and spread spectrum communication. Digital watermarks represent a commercial application of steganography. Watermarks can be used to track the copyright and ownership of electronic media. In this volume, the authors focus on techniques for hiding information in digital media. They analyze the hiding techniques to uncover their limitations. These limitations are employed to devise attacks against hidden information.